2010
DOI: 10.3945/jn.109.117374
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Bifidobacteria Levels Are Associated with the Inflammatory Response in Magnesium-Deficient Mice

Abstract: Magnesium (Mg) deficiency is a common nutritional disorder that is linked to an inflammatory state characterized by increased plasma acute phase protein and proinflammatory cytokine concentrations. Recent studies have shown that changes in the composition of gut microbiota composition participate in systemic inflammation. In this study, therefore, we assessed the potential role of gut microbiota in intestinal and systemic inflammation associated with Mg deficiency in mice. For this purpose, mice were fed a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 40 publications
6
67
0
3
Order By: Relevance
“…Experimental magnesium deficiency induces an inflammatory syndrome in animal models, characterized by macrophage and white blood cell activation, release of proinflammatory cytokines, activation of an acute-phase response and excessive production of ox- ygen-free radicals [42,43] . In this study, in patients with CRP ≤ 5 mg/dl, there was a negative correlation between magnesium and inflammation (measured by CRP serum levels).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental magnesium deficiency induces an inflammatory syndrome in animal models, characterized by macrophage and white blood cell activation, release of proinflammatory cytokines, activation of an acute-phase response and excessive production of ox- ygen-free radicals [42,43] . In this study, in patients with CRP ≤ 5 mg/dl, there was a negative correlation between magnesium and inflammation (measured by CRP serum levels).…”
Section: Discussionmentioning
confidence: 99%
“…Mg supplementation improves myocardial metabolism and inhibits myocardial cell death. Thus, it enhances vascular tone, cardiac output, and afterload, and reduces cardiac arrhythmias (Lin et al 2010;Pachikian et al 2010). Another study indicated that Mg supplementation improves lipid metabolism and reduces vulnerability to oxygen-derived free radicals (Dickens et al, 1992;Shechter, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although a diet high in dietary fiber-containing foods would undoubtedly also be high in these micronutrients, which was noted by significant correlations among intakes such nutrients, it is nevertheless interesting to consider the dependence of the gut microbiota not only on dietary fiber but also on dietary vitamins and minerals as well. Only a fraction of the vitamins and minerals consumed in the diet are absorbed in the small intestine [34]; therefore, many of these nutrients make their way to the large bowel where they influence the gut microbiota [35][36][37][38]. Because of the dense microbial community in this region, it is likely that these nutrients would be in high demand and the less adaptable bacteria would be more susceptible to lack of these compounds.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the dense microbial community in this region, it is likely that these nutrients would be in high demand and the less adaptable bacteria would be more susceptible to lack of these compounds. Based on literature data, we might speculate that these vulnerable bacteria would be those bacteria that are considered beneficial, including bifidobacteria and the butyrate producers [6,7,35].…”
Section: Discussionmentioning
confidence: 98%